STUDI PEMANFAATAN ROTAN OLEH MASYARAKAT DUSUN KEBAK RAYA DI KAWASAN HUTAN DESA SURUH TEMBAWANG KECAMATAN ENTIKONG KABUPATEN SANGGAU - Utami, Sri; Wardenaar, Evi; Idham, M (Universitas Tanjungpura, 2017)
Forest in indonesia has a Â potential of non-timber forest products. Non-Timber Forest Products (NTEP) are still less optimally utilized because forest management has been oriented to timber forest products. Rattan is one source of biodiversity in Indonesia and is the result of non-timber forest potential. In rural areas, rattan is used by the community as a woven material, ropes, etc. This study aims to determine the economic values of rattan used by the community, determine the species of rattan used by the community and determine the number of derivative products genered by the people in Suruh Tembawang village, Sanggau regency. This research used a descriptive method involving the community as respondents. The results showed that there are five species of rattan that ordinary people use for woven materials such as Arit Rattan,Â Saga Rattan, Manau Rattan, Udang Rattan and Semut Rattan. The products are usually sold at a price of for bidai weaving,Â for penyakin weaking and for bakul weaking.